HUBUNGAN ANTARA KARAKTERISTIK DEMOGRAFI DENGAN STIGMA PUBLIK TERHADAP PENDERITA GANGGUAN JIWA DI DUSUN DEMEN KECAMATAN PAKEM SLEMAN YOGYAKARTA - Enip Sekar Sulistyani; Dewi Retno Pamungkas; Puji Sutarjo (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Mental disorders are t h e manifestations of deviant behaviors due to emotional distortion. Stigma is a distorted assessment that leads to isolation and ignorance of people with mental illness. Objectives: To investigate the relationship between demographic characteristics and public stigma towards people with mental disorders in Demen district, Pakem Sleman Yogyakarta. Methods: The study used descriptive correlation methods. The population in this study were all residents of Demen district, who aged >25 years. The sampling technique was cluster sampling with 200 respondents. Data were collected with a questionnaire. Analysis of the data used chi-square test and Kendall’s Tau. Results: There was no relationship between gender characteristics with public stigma towards people with mental disorders with p= 0.173 (p>0.05). There was a relationship between education level with the public stigma towards people with mental disorders with p= 0.016 (p<0.05). There was a relationship between socio-economic level with the public stigma towards people with mental disorders with p= 0.024 (p<0.05). Conclusion: There was a relationship between education and socio-economic level with public stigma towards people with mental disorders. Keywords: Demographic characteristics, stigma, mental disorders